The Effect of Compost Based on Water Hyacinth and NPK Fertilizer on the Growth of Cayenne Pepper (Capsicum frutescens L.) - Lale Agiet Safitri; Prapti Sedijani; Ahmad Raksun (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Continuous fertilization with inorganic fertilizers causes the soil to become hard and the balance of nutrients in the soil becomes disrupted so that the soil is unable to provide sufficient nutrients to support normal plant growth. This study aims to determine the effect of compost made from water hyacinth, NPK fertilizer, and their combinations on the growth of cayenne pepper plants, and to determine the best dosage of fertilizer on the growth response of cayenne pepper plants. This study used a completely randomized design (CRD) which consisted of 2 factors. Type of fertilizer and dose of fertilizer with each 4 levels of fertilization and 3 repetitions. The results of data analysis using the ANOVA test showed that the application of water hyacinth-based compost fertilizer; NPK fertilizer; and the combination can increase plant height, number of leaves, leaf area, fresh weight and dry weight on cayenne pepper plants. The DMRT test at the 5% level showed that the best treatment for plant height, wet weight and dry weight was a dose of 400 gr compost and 0 gr NPK, while the best treatment for leaf count was a dose of 200 gr compost and 0.4 gr NPK and the best treatment for Leaf area is a dose of 0 gr compost and 0.4 gr NPK.